Contemporary prostate cancer treatment choices in multidisciplinary clinics referenced to national trends. Issue 3 (19th November 2019) - Tang, Chad; Hoffman, Karen E.; Allen, Pamela K.; Gabel, Molly; Schreiber, David; Choi, Seungtaek; Chapin, Brian F.; Nguyen, Quynh‐Nhu; Davis, John W.; Corn, Paul; Logothetis, Christopher; Ward, John; et al.
Abstract : Background: The purpose of this study was to assess treatment choices among men with prostate cancer who presented at The University of Texas MD Anderson Cancer Center multidisciplinary (MultiD) clinic compared with nationwide trends. Methods: In total, 4451 men with prostate cancer who presented at the MultiD clinic from 2004 to 2016 were analyzed. To assess nationwide trends, the authors analyzed 392, 710 men with prostate cancer who were diagnosed between 2004 and 2015 from the Surveillance, Epidemiology, and End Results (SEER) database. The primary endpoint was treatment choice as a function of pretreatment demographics. Results: Univariate analyses revealed similar treatment trends in the MultiD and SEER cohorts. The use of procedural forms of definitive therapy decreased with age, including brachytherapy and prostatectomy (all P  < .05). Later year of diagnosis/clinic visit was associated with decreased use of definitive treatments, whereas higher risk grouping was associated with increased use (all P  < .001). Patients with low‐risk disease treated at the MultiD clinic were more likely to receive nondefinitive therapy than patients in SEER, whereas the opposite trend was observed for patients with high‐risk disease, with a substantial portion of high‐risk patients in SEER not receiving definitive therapy. In the MultiD clinic, African American men with intermediate‐risk and high‐risk disease were more likely to receive definitive therapy than white men, but for SEER the opposite was true. Conclusions: Presentation at a MultiD clinic facilitates the appropriate disposition of patients with low‐risk disease to nondefinitive strategies of patients with high‐risk disease to definitive treatment, and it may obviate the influence of race. Abstract : Presentation at a multidisciplinary clinic facilitates the appropriate disposition of low‐risk patients into nondefinitive strategies and of high‐risk patients into definitive treatment, and it may obviate the confounding influence of race. By comparison, nationwide, the disposition of patients may be confounded by pretreatment demographic factors.